Favorable Outcomes in Blunt Chest Injury with Noninvasive Bi-Level Positive Airway Pressure Ventilation. Issue 7 (July 2017) - Udekwu, Pascal; Patel, Sahill; Farrell, Meagan; Vincent, Rhonda
Recent clinical research in patients with blunt chest injury has focused on the benefits of surgical fixation of rib fractures. Noninvasive ventilation (NIV) has been demonstrated to prevent the need for intubation and ventilation in posttraumatic respiratory failure. The preemptive use of NIV in patients with rib fractures has not been extensively studied. Our study evaluated the outcomes of patients with ≥3 rib fractures and hospitalized for ≥ 4 days. Seventy-one patients treated with NIV were compared with 270 patients without NIV. NIV patients were older (65.8 vs 56.5 years) had more rib fractures (6.25 vs 5.32) and a higher body mass index (31 vs 27.8) than the comparison group, P < 0.05, but did not have an increased mortality or incidence of respiratory failure. NIV patients did have a statistically significant increase in length of stay compared to control (12.8 vs 8.8, P < 0.05). In the total sample, worse clinical outcomes were associated with older age, increased number of and bilateral rib fractures, higher Injury Severity Score, lower Glasgow Coma Scale, and higher body mass index. Outcomes in the most severely injured group of patients treated with NIV were comparable to other studies using surgical fixation of rib fractures and epidural pain control.